A passion for beef: Post-domestication changes in cattle body size in China from the Late Neolithic to the Late Bronze Age - Yu, Chong; Zhao, Hao; Hu, Songmei; Yang, Miaomiao; Guo, Xiaoning; Ng, Chuenyan (Frontiers in Ecology and Evolution, 2022)
The introduction and the later dispersal of domestic cattle in China had played an enormous part in food production, handicraft manufacture and ritual activities. However, we lack the details of pastoral economies, herding strategies and utilization patterns of cattle in ancient China. This study, for the first time, use biometrical assessments to investigate post domesticated cattle husbandry and how it changed over time. Biometric data from 8 sites dating from the Late Neolithic to the Late Bronze Age was evaluated using the kernel analysis and mixture analysis. Results indicated that the general body size of cattle first decrease than increase. By combining the estimated distribution of male and female individuals, we can see that sex ratios affect size variation during Bronze Age times. Although no breed improvement has been detected so far, the herding and slathering strategies over time is different.